The microbial abundance dynamics of the paediatric oral cavity before and after sleep. Issue 1 (1st January 2020) - Carlson-Jones, Jessica A. P.; Kontos, Anna; Kennedy, Declan; Martin, James; Lushington, Kurt; McKerral, Jody; Paterson, James S.; Smith, Renee J.; Dann, Lisa M.; Speck, Peter; Mitchell, James G.
ABSTRACT: Objective : Microhabitats in the oral cavity differ in microbial taxonomy. However, abundance variations of bacterial and viral communities within these microhabitats are not fully understood. Aims and Hypothesis : To assess the spatial distribution and dynamics of the microbial abundances within 6 microhabitats of the oral cavity before and after sleep. We hypothesise that the abundance distributions of these microbial communities will differ among oral sites. Methods : Using flow cytometry, bacterial and virus-like particle (VLP) abundances were enumerated for 6 oral microhabitats before and after sleep in 10 healthy paediatric sleepers. Results : Bacterial counts ranged from 7.2 ± 2.8 × 10 5 at the palate before sleep to 1.3 ± 0.2 × 10 8 at the back of the tongue after sleep, a difference of 187 times. VLPs ranged from 1.9 ± 1.0 × 10 6 at the palate before sleep to 9.2 ± 5.0 × 10 7 at the back of the tongue after sleep, a difference of 48 times. Conclusion : The oral cavity is a dynamic numerically heterogeneous environment where microbial communities can increase by a count of 100 million during sleep. Quantification of the paediatric oral microbiome complements taxonomic diversity information to show how biomass varies and shifts in space and time.